Does inventor centrality foster regional innovation? The case of the Swiss medical devices sector. Issue 8 (3rd August 2017) - Coffano, Monica; Foray, Dominique; Pezzoni, Michele
ABSTRACT: Does inventor centrality foster regional innovation? The case of the Swiss medical devices sector. Regional Studies . This paper contributes an empirical analysis to the discussion of the impact of inventors' collaboration networks on regional innovation. More precisely, it investigates how inventors' degree centrality in the regional co-invention network, and inventors' cross-regional linkages, influence innovation in the Swiss medical devices sector. The results show that high values of inventor centrality and the presence of cross-regional linkages have mutually reinforcing effects on innovation. These findings provide insights for policy-makers designing policy to encourage regional innovation.